Early‐onset leukoencephalomyelopathy due to a biallelic NDUFV1 variant in a mid‐forties patient. Issue 6 (28th April 2022) - Gschwind, Markus; Garcia Segarra, Nuria; Schaller, André; Bolognini, Ramona; Nuoffer, Jean‐Marc; Hourez, Raphael; Deprez, Manuel; Lhermitte, Benoit; Maeder, Philippe; Tran, Christel; Kuntzer, Thierry
Abstract: We present a patient who developed, after an early‐onset, a stable course of spastic paraplegia and ataxia for 4 decades and eventually succumbed to two episodes of postinfectious lactic acidosis. Diagnostic workup including muscle biopsy and postmortem analysis, oxymetric analysis, spectrophotometric enzyme analysis, and MitoExome sequencing revealed a necrotizing leukoencephalomyelopathy due to the so far unreported biallelic variant of the NDUFV1 gene (p.(Pro122Leu)). This case extends our understanding of NDUFV1 variants with a 14‐fold longer lifetime than so far reported cases, and will foster sensitivity toward respiratory chain disease also in adult patients with sudden deteriorating neurological deficits.